2011
DOI: 10.1371/journal.pbio.1000587
|View full text |Cite
|
Sign up to set email alerts
|

A c-di-GMP Effector System Controls Cell Adhesion by Inside-Out Signaling and Surface Protein Cleavage

Abstract: In Pseudomonas fluorescens Pf0-1 the availability of inorganic phosphate (Pi) is an environmental signal that controls biofilm formation through a cyclic dimeric GMP (c-di-GMP) signaling pathway. In low Pi conditions, a c-di-GMP phosphodiesterase (PDE) RapA is expressed, depleting cellular c-di-GMP and causing the loss of a critical outer-membrane adhesin LapA from the cell surface. This response involves an inner membrane protein LapD, which binds c-di-GMP in the cytoplasm and exerts a periplasmic output prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
308
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(331 citation statements)
references
References 37 publications
22
308
0
1
Order By: Relevance
“…Another example involves the GGDEF-EAL c-di-GMP receptor LapD from Pseudomonas fluorescens (166,167). While neither the GGDEF nor EAL domain of this receptor is enzymatically active, c-di-GMP binds to the degenerate EAL domain of LapD with a high affinity (68,166). The Bacillus subtilis EAL-YkuI_C protein YkuI (BSU14090) is another candidate receptor belonging to this class.…”
Section: Types Of C-di-gmp Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example involves the GGDEF-EAL c-di-GMP receptor LapD from Pseudomonas fluorescens (166,167). While neither the GGDEF nor EAL domain of this receptor is enzymatically active, c-di-GMP binds to the degenerate EAL domain of LapD with a high affinity (68,166). The Bacillus subtilis EAL-YkuI_C protein YkuI (BSU14090) is another candidate receptor belonging to this class.…”
Section: Types Of C-di-gmp Receptorsmentioning
confidence: 99%
“…However, the membrane fusion protein domain present in the periplasmic fragment of Alg44 suggests that it is involved in protein-protein interactions within the alginate translocation complex. Deletion of a short C-terminal sequence abolished alginate polymerization (157), suggesting that c-di-GMP binding to the cytoplasmic PilZ domain of Alg44 can be transferred via an inside-out signaling mechanism (67,68) to the periplasmic domain to activate alginate polymerization.…”
Section: Regulation Of Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the presence of external elements present in the environment, such as salts, was also shown to influence bioadhesion and biofilm formation. Recent studies demonstrated that the presence of inorganic phosphate played a key role in the biofilm formation of Pseudomonas fluorescens and depending of the level found in the environment, determined the adhesive action of LapA, an adhesin localized outside the bacterial cell membrane [44,63].…”
Section: Bacterial Surface Structurementioning
confidence: 99%
“…As functional and dynamic communities, biofilms are able to modify the matrix components and remodel their structures and functions as an adaptive strategy to encounter the fluctuation of various environment conditions as well as stresses. Protease and nuclease have been recently reported to be secreted by biofilm cells, which leads to disruption of protein adhesions and eDNA of biofilm matrix, resulting in remodeling of the biofilm architectures [10][11][12]. However, little is known about the biofilm self-generated factors that target the essential and universal matrix component, exopolysaccharide.…”
Section: Introductionmentioning
confidence: 99%